2018
DOI: 10.18488/journal.1.2018.812.1157.1169
|View full text |Cite
|
Sign up to set email alerts
|

Work-Family Conflict and Job Satisfaction: Does Organisational Support Matter?

Abstract: This study attempts to examine the moderation effects of organisational supports in the relationships between Work Family Conflict (WFC) and Job Satisfaction (JS) / Family Work Conflict (FWC) and Job Satisfaction (JS). The collection of data from 303 respondents who are academicians of private universities in Bangladesh was with aid of the convenience sampling technique. Multi-group analysis with the adoption of the Covariance Based-Structural Equation Modelling (CB-SEM) technique was used to complete the anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 34 publications
2
8
0
Order By: Relevance
“…JS. With a view to understanding and gaining the knowledge for finding out the relationship between W to FC and JS in a better way, it has been explored in various occupations, fields and even different cultures (Rahman et al, 2019(Rahman et al, , 2018Bakalım and Karçkay, 2017;Kalliath and Kalliath, 2013;Anafarta, 2011 association between W to FC and satisfaction. Different meta-analyses also showed that W to FC harms satisfaction (life, job and family).…”
Section: Theoretical Foundation and Hypotheses Developmentmentioning
confidence: 99%
“…JS. With a view to understanding and gaining the knowledge for finding out the relationship between W to FC and JS in a better way, it has been explored in various occupations, fields and even different cultures (Rahman et al, 2019(Rahman et al, , 2018Bakalım and Karçkay, 2017;Kalliath and Kalliath, 2013;Anafarta, 2011 association between W to FC and satisfaction. Different meta-analyses also showed that W to FC harms satisfaction (life, job and family).…”
Section: Theoretical Foundation and Hypotheses Developmentmentioning
confidence: 99%
“…Being able to meet the demands of a job, doing all tasks well is an obligation that must be fulfilled. The results of this study indicate that professionalism is needed in carrying out a job while also having to take care of the family, as research conducted by (Rahman et al, 2018) and states that female workers who are married have multiple roles, have responsibilities both for work and for their families (Boyar et al, 2003). Especially when working from home, there is a role conflict.…”
Section: Discussionmentioning
confidence: 74%
“…The development of study related to Work-Family Conflict (WFC) has been done by several researchers, such as the research about WFC related to the role (Ryan, Ma, & Ku, 2009), work demand, and turnover intention (Boyar, Maetz, Jr, Pearson, & Keough, 2003;Asghar, Gull, Bashir, & Akbar, 2018), work demand and job satisfaction (Boles, Howard, & Donofrio, 2001;Rahman et al, 2018), and work demand and stress, exhaustion (Boyar et al, 2003). Those researches show that many researchers interested in studying the woman who has double roles have a responsibility both for her work and family.…”
Section: Introductionmentioning
confidence: 99%
“…Although limited attention is paid to relationship between FWAs, WLC and job satisfaction, some attempts were developed in this perspective showing that employees who have flexible work and experienced less conflict between work and family tend to carry positive aspects from daily life to their job (Obrenovic et al, 2020). In other words, the more individuals feel balanced the more they enjoy their daily life and their work (Qu & Zhao, 2012;Rahman et al, 2018).…”
Section: Moderating Role Of Work-life Conflict and Work Pressurementioning
confidence: 99%